FORMULASI DAN EVALUASI LIP BALM LIOFILISAT BUAH TOMAT (SOLANUM LYCOPERSICUM L.) SEBAGAI PELEMBAB BIBIR - Nurul Arfiyanti Yusuf; Besse Hardianti; Indah Ayu Lestari; Amriani Sapra (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2019)
The research on formulation and evaluation of lypholized tomato (Solanum lycopersicum L) as lip balm has been conducted. The objective of this research was to investigate the physical stability of lip balm formula from lypholized tomato that could enhance the lips’ humidity. The formulation of lip balm was made into three concentration i.e 1%, 3%, and 5%. The physical stability evaluations that were performed before and after stress condition. Which is included organoleptic, homogeneity, and melting point test. The stable formula was then evaluated as skin moisture enhancer using skin analyzer. The results of this research showed that all three formula was physically stable. On the third formula (lypholized concentration of 5%) had the highest percentation of moisture enhancement with the significant difference among the three formulas.